EXTENT ENTREPRENEURSHIP EDUCATION INFLUENCES THE ENTREPRNEURIAL INTENTIONS OF BUSINESS EDUCATION UNDERGRADUATES IN UNIVERSITIES IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study determined the extent entrepreneurship education influences theentrepreneurial intentions of business education undergraduates in universities inAnambra State. Two research questions guided the study and two null hypotheseswere tested at 0.05 level of significance. The design of the study was descriptivesurvey. Population of the study was 619 (226 male and 393 female) businesseducation undergraduates in the three universities in Anambra State offering theprogramme. The stratified random sampling and simple random sampling techniqueswere used to select a sample size of 243 (male and female) students. An adaptedEntrepreneurial Intention Questionnaire (EIQ) developed by Linan and Chen (2009)was used to collect data for the study. The questionnaire was a 5-point scalecontaining 37 items in four clusters which was validated by experts in the field ofBusiness Education and Measurement and Evaluation. The reliability of theinstrument was determined using the Cronbach Alpha co-efficient which yieldedvalues of 0.97, 0.80, 0.71, and 0.75 respectively for the four clusters and overall valueof 0.80. Mean and standard deviation were used to analyze data to answer theresearch questions and determine the cohesiveness or otherwise of respondents’ meanratings. The z-test was used to test the null hypotheses at 0.05 level of significance.The findings revealed that entrepreneurship education influenced attitude andperceived behavioural control of business education undergraduates towardsbecoming entrepreneurs to a great extent. Gender did not significantly influence therespondents’ mean ratings in all the contents covered. It was concluded that businesseducation undergraduates in universities in Anambra State would benefit fromeffectively delivered entrepreneurship education programme as it would improve theirentrepreneurial intention. Based on these findings, it was recommended among othersthat university authorities should assist business education undergraduates thatindicate intention to become entrepreneurs while in school and after graduationthrough incubator programmes.
Keywords: Entrepreneurship Education, Entrepreneurial Intentions, Business Education